Substituent effects on the thermal decomposition of phosphate esters on ferrous surfaces - Ewen,JP; Ayestarán,Latorre C; Gattinoni,C; Khajeh,A; Moore,JD; Remias,J; Martini,A; Dini,D (The Journal of Physical Chemistry C, 2020)
Phosphate esters have a wide range of industrial applications, for example in tribology where they are used as vapour phase lubricants and antiwear additives. An atomic-level understanding of phosphate ester tribofilm formation mechanisms is required to improve their tribological performance. A process of particular interest is the thermal decomposition of phosphate esters on steel surfaces, since this initiates polyphosphate film formation. In this study, reactive force field (ReaxFF) molecular dynamics (MD) simulations are used to study the thermal decomposition of phosphate esters with different substituents on several ferrous surfaces. The ReaxFF parameterisation was validated for a representative system using density functional theory (DFT) calculations. During the MD simulations on Fe3O4(001) and α-Fe(110), chemisorption interactions between the phosphate esters and the surfaces occur even at room temperature, and the number of molecule-surface bonds increases as the temperature increases from 300 to 1000 K. Conversely, on hydroxylated, amorphous Fe3O4, most of the molecules are physisorbed and some desorption occurs at high temperature. Thermal decomposition rates were much higher on Fe3O4(001) and particularly α-Fe(110) compared to hydroxylated, amorphous Fe3O4. This suggests that water passivates ferrous surfaces and inhibits phosphate ester chemisorption, decomposition, and ultimately polyphosphate film formation. For the alkyl phosphates, thermal decomposition proceeds mainly through C-O and C-H cleavage on Fe3O4(001). Aryl phosphates show much higher thermal stability, and decomposition on Fe3O4(001) only occurs through P-O and C-H cleavage, which require very high temperature. The onset temperature for C-O cleavage on Fe3O4(001) increases as: tertiary alkyl < secondary alkyl < primary linear alkyl ≈ primary branched alkyl < aryl. This order is consistent with experimental observations for the thermal stability of antiwear addi